Stability analysis of closed loop TRMS with observer based reliable H infinity controller using Kharitonov’s stability theorem - S. Rao, Vidya; I. George, V; Kamath, Surekha; Shreesha, C (International Journal of Engineering and Technology, 2018)
The laboratory Twin Rotor Multiple Input Multiple Output System (TRMS) serving as a model of a helicopter has un modeled errors in its model, due to linearization, measurement errors, equipment wear, sensors or/and actuator failures. This mismatch is termed as uncertainties in the model. Due to sensor and actuator failure there would exist a large range of uncertainties. In this paper, the range of robust stability bound for closed loop TRMS along with observer based reliable H infinity controller using Kharitonovâ€™s stability theorem is found. The variation in parameters of TRMS from its nominal values are shown. The Kharitonovâ€™s stability analysis on TRMS proves that within the mentioned uncertainty limit the TRMS along with observer based reliable H infinity controller gives the closed loop stable response.Â